2007
DOI: 10.1093/europace/eum053
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous SCN5A mutation in Brugada syndrome with monomorphic ventricular tachycardia and structural heart abnormalities

Abstract: This study provides the first evidence of a homozygous missense mutation in SCN5A associated with atypical ventricular arrhythmias and right structural abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
1
25
0
4
Order By: Relevance
“…The mutation of the corresponding residues in Na v 1.5 (R814Q and R814W) are linked to DCM phenotypes. 2,6,16 The similar localization of the periodic paralysis linked mutations in Na v 1.4 and DCM linked mutations in Na v 1.5 ( Fig. 1) prompted us to further examine the spatial localization of those mutations.…”
Section: Mutations In the Channel's Vsds Could Be Linked To Dcm Via Tmentioning
confidence: 80%
“…The mutation of the corresponding residues in Na v 1.5 (R814Q and R814W) are linked to DCM phenotypes. 2,6,16 The similar localization of the periodic paralysis linked mutations in Na v 1.4 and DCM linked mutations in Na v 1.5 ( Fig. 1) prompted us to further examine the spatial localization of those mutations.…”
Section: Mutations In the Channel's Vsds Could Be Linked To Dcm Via Tmentioning
confidence: 80%
“…The pathological study of Frustaci et al 11 showed evidence of myocardial damage in patients with Brugada syndrome and SCN5A mutations. Most recently, a new homozygous mutation, R814Q, was reported 12 to be associated with Brugada syndrome and right ventricular structural abnormalities. Although not all SCN5A mutations that are linked to myocardial damage and structural abnormalities have been functionally studied in vitro, those that have been studied generally are characterized by reduced Na ϩ currents or a phenotype known as loss of function.…”
Section: Editorial See P 80 Clinical Perspective See P 92mentioning
confidence: 99%
“…9, 10 The pathogenic mechanisms of SCN5A-associated DCM, arrhythmia-mediated cardiomyopathy, disordered intracellular sodium homeostasis, and the disruption of sodium channel-protein interactions were discussed previously. 33 An investigation into disordered intracellular sodium homeostasis in isolated guinea pig CMs found that sodium currents contributed to the generation of calcium transients by the sarcoplasmic reticulum via the reversemode sodium-calcium exchanger, 34 suggesting that SCN5A loss-of-function mutations might reduce the amplitude of calcium transients, resulting in negative cardiac inotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…2 Additionally, in rare cases, SCN5A mutations are associated with dilated cardiomyopathy (DCM). 9, 10 The SCN5A missense mutation, D1275N, has been associated with several unusual phenotypes associated with reduced sodium channel function, including DCM, SND, CCD, and atrial and ventricular tachyarrhythmias. 11- 13 The reported electrophysiological properties of SCN5A-D1275N channels vary with experimental system; studies using heterologous expression systems showed no major differences between the mutant and wild-type (WT) channels, 14,15 whereas peak sodium current densities were reduced in SCN5A-D1275N knock-in mice than in WT ones.…”
Section: Human-induced Pluripotent Stem Cell (Hipsc) Generation and Cmentioning
confidence: 99%